Personal Hygiene Analysis, Environmental Sanitation and Skin Health Complaints In Inmates At Class IIA Medan Women's Correctional Institution in 2020 - Dina Tania Gultom; Irna Marsaulina (Indonesian Journal of Medical Anthropology, 2021)
Analysis of Personal Hygiene, Environmental Sanitation and Skin Health Complaints in Inmates at The Class IIA Medan Women's Correctional Institution. This type of research is quantitative research that is descriptive survey. The research was conducted from September 2019 to September 2020 at the Medan Class IIA Women's Correctional Institution. Samples from this study were 86 people. However, personal hygiene of inmates belongs to the bad category with the highest proportion in terms of cleanliness of the use of beds and bed linen (50%), but environmental sanitation conditions in the Medan Class IIA Women's Correctional Institution are included in the criteria of eligibility.